DYNAMIC YOUNG'S MODULUS AND FLEXURAL STRENGTH OF SEA ICE. - Frankenstein,Guenther; Garner,Robert (1970)
The report describes the results of tests made to determine the dynamic Young's modulus E of young sea ice. The ice samples were mainly parallelepipeds but a few were 7.62-cm-diam cores. The longitudinal wave velocity was determined by measuring the time required for a sound wave to travel the length of the sample. The flexural strength of the ice was determined by conducting a number of simple beam tests. The average value for the flexural strength was 11.3 kg/sq cm. (Author)